2012
DOI: 10.1097/qad.0b013e3283519371
|View full text |Cite
|
Sign up to set email alerts
|

Novel clinical trial designs for the development of new antiretroviral agents

Abstract: The resounding success of combination antiretroviral efficacy for both treatment-naïve and -experienced patients – with 70% – 90% viral suppression rates in recent studies–has made registration trials for new agents challenging. With the inevitable specter of drug resistance, new agents must have a pathway to approval. The Forum for Collaborative HIV Research obtained input from concerned stakeholders including industry, clinical sciences, community advocacy and regulatory sciences (Food and Drug Administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…The protocolspecified noninferiority margin is intended to reflect the maximum clinically acceptable difference between the therapeutic alternatives, as well as to prevent successive erosion of efficacy as new agents become the old standards in future trials [30][31][32]. In reality, however, the margin is mostly driven by logistical considerations around sample size and power calculations [2,19,31,[33][34][35]. In addition wide margin increases the probability of lying in a difficult situation in which the entire 95% CI lied within the noninferiority margin and the 0 bound [30,36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The protocolspecified noninferiority margin is intended to reflect the maximum clinically acceptable difference between the therapeutic alternatives, as well as to prevent successive erosion of efficacy as new agents become the old standards in future trials [30][31][32]. In reality, however, the margin is mostly driven by logistical considerations around sample size and power calculations [2,19,31,[33][34][35]. In addition wide margin increases the probability of lying in a difficult situation in which the entire 95% CI lied within the noninferiority margin and the 0 bound [30,36].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of HAART has led to a move towards the use of noninferiority designs for HIV drug development [1,2]. Indeed, with viral suppression rates of 80-90% in recent studies, it would be difficult to design a superiority trial showing any meaningful improvement.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This approach may provide an alternative route for regulatory assessment of new antiretroviral drugs. Recently, Mani et al, 15 suggested clinical trial design options for the development of new antiretroviral agents for treatment-experience patients. The authors proposed that efficacy of a new antiretroviral drug in treatment-experience patients could be examined by comparison to placebo as an add-on to a failing regimen for a 10e14 day period followed by initiation of a new OBT in both arms of the study with the investigational antiretroviral drug given to all the subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term placebo-controlled comparisons are also not appropriate because continued use of an unmodified failed ARV regimen would increase the risk of emergent resistance to the investigational drug and progression of disease. The BRIGHTE study was designed to address these challenges in accordance with guidance on the development of ARVs for the HTE population [10,11]. Building on data from a phase 2b study (ClinicalTrials.gov, NCT01384734) that had demonstrated favorable efficacy, safety, and tolerability of fostemsavir in treatment-experienced PLWH [12,13], BRIGHTE aimed to further assess the efficacy and safety of fostemsavir and also to fulfill the crucial unmet medical needs of HTE PLWH.…”
Section: The Brighte Clinical Study Design Was Appropriate For Hte Plwhmentioning
confidence: 99%